Peculiarities of vegetative regulation of heart rate in wrestlers of different age groups - E.B. Zapovitriana; G.V. Korobeynikov; L.G. Korobeinikova (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : the aim of the work was to study the characteristics of vegetative regulation of cardiac rhythm in athletes of high qualification of different age groups. Material : 26 wrestlers of Greco-Roman style of high qualification aged 19-34 years old were studied. Vegetative regulation was assessed by statistical analysis of heart rate variability using cardiac monitors «Polar RS800CX». Results : the results showed that the wrestlers of older age group has a greater level of tension of regulation of heart rhythm for compared with young athletes. This is confirmed by the reduced values of the mean square deviation RR- intervals and triangular index. According to the results of spectral analysis of cardio revealed activation of parasympathetic tone of the autonomic regulation of the heart rhythm of wrestlers in older age group, compared with young athletes. The increase of tension of regulation of heart rate in the wrestlers of older age group accompanied by a slowdown of aperiodic and periodic oscillations of cardio intervals. Conclusions: the high level of tension of regulation of heart rhythm in older wrestlers group (26-34) accompanied by the activation of neurohumoral centers and parasympathetic link of vegetative nervous system.